Clinical Analysis of Preoperative Anti-thyroglobulin Antibody in Papillary Thyroid Cancer Between 2011 and 2015 in Beijing, China: A Retrospective Study - Jia, Xiaomeng; Pang, Ping; Wang, Lin; Zhao, Ling; Jiang, Lina; Song, Yeqiong; Fan, Xiaojing; Wang, Yajing; Zhao, Sitong; Ba, Jianming; Yang, Guoqing; Wang, Xianling; et al. (Frontiers in Endocrinology, 2020)
It has been suggested that anti-thyroglobulin antibody (TgAb) are more common among papillary thyroid cancer (PTC). This study investigated the correlation between TgAb expression level and PTC in Chinese patients between 2011-2015 in a retrospective study. Thyroid goiter patients who have undergone thyroidectomy and received a confirmed pathological diagnosis were enrolled into this retrospective study. Demographic data, clinical characteristics and preoperative thyroglobulin antibody (TgAb) were collected from each patient. Based on the TgAb test, patients were divided into a TgAb negative (TgAb-) group (<60 IU/mL) and a TgAb positive (TgAb+) group (≥60 IU/mL), Among 4046 patients, 671 patients were TgAb+ while 3375 patients were TgAb-. In the TgAb+ group, there were 535 (79.7%) patients with PTC. In the TgAb- group, there were 2154 (63.8%) patients with PTC. The malignancy rate was significantly higher in TgAb+ patients than in TgAb- patients. TgAb+ patients were divided into four groups based on the TgAb titer by quartile stratification. The prevalence of PTC did not increase with TgAb titer. No significant difference in TgAb expression was noted in patients with different clinicopathologies, including TNM stage, lymph node metastasis and multifocal carcinoma. Regression analysis suggested a higher risk of PTC malignancy among TgAb+ patients. Preoperative TgAb expression levels ≥60 IU/mL might be associated with a higher risk of PTC. However, there was not a titer-dependent association between elevated TgAb titer and PTC malignancy.